From natural gas to hydrogen: What are the rules for European gas network decarbonisation and do they ensure flexibility and security of supply? - Katja Yafimava (The Oxford Institute for Energy Studies, 2024)
On 11 April 2024 the European Parliament adopted the Renewable and Natural Gases and Hydrogen (RNGH) Directive and the RNGH Regulation - otherwise known as the Decarbonised Gas and Hydrogen Package - and published both documents on 12 April 2024. Once approved by the Council and published in the EU Official Journal - expected by June - the Package, together with the TEN-E Regulation, will constitute the new regulatory framework, governing construction of, and access to, hydrogen networks, and the re-purposing and de-commissioning of, and access to, natural gas networks in the EU. This paper analyses the impact of this framework on the existing natural gas networks and the emerging hydrogen network, and seeks to establish specifically whether its rules ensure flexibility and security of supply. The paper concludes that although regulatory flexibility is built into the framework by establishing a transition implementation period, allowing exemptions and derogations for existing and new hydrogen infrastructure, and enabling financial and regulatory support via a PCI/PMI status, it is far from certain to be sufficient to enable the EU hydrogen market to develop at scale. The framework also does not guarantee that phasing in hydrogen networks and phasing out natural gas networks - either through re-purposing or de-commissioning - will be carried out in a coordinated manner across the EU, without negatively affecting the security of natural gas supply. Overall, the framework appears to be built on the premise that the EU hydrogen market will develop fast and at scale but lacks a 'safety cushion'. In particular, it does not guarantee the coordinated re-purposing of the natural gas networks that could still be needed should the hydrogen market roll-out be slower and more gradual. The framework could of course be adjusted and will continue to remain 'work in progress' at least until 2030 as more rules are established in the upcoming network codes in the 2020s, as the hydrogen market rolls out (or fails to do so).
Keywords: 330; Coordination; decarbonisation; Decommissioning; derogations; ENNOH; ENTSOG; exemptions; Flexibility; Hydrogen; Natural gas; NDP; network codes; Networks; PCI; PMI; renewable and natural gas and hydrogen directive; renewable and natural gas and hydrogen regulation; repurposing; Security of supply; TEN-E Regulation; topology; TYNDP